1993
DOI: 10.1002/dev.420260506
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress has long‐term effects on behavioral responses to stress in juvenile rhesus monkeys

Abstract: The effect of maternal psychological disturbance during pregnancy on postnatal responses of the offspring to stressful events was investigated in juvenile rhesus monkeys. Six pregnant monkeys were repeatedly removed from their home cages and briefly exposed to unpredictable noise during mid to late gestation (Days 90-145 postconception). Six undisturbed pregnant mothers served as controls. Behavioral data were later collected from the 18-month-old offspring under a baseline and four progressively stressful con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(89 citation statements)
references
References 38 publications
4
84
0
1
Order By: Relevance
“…For example, findings from several studies have shown that environmental complexity can augment brain development (e.g., van Praag, Emperman, & Gage, 2000;Rosenweig & Bennett, 1996). In contrast, environmental deprivation and stress have been shown to adversely affect behavior (Clarke & Schneider, 1993;Higley et al, 1993), performance on cognitive tests (Francis, Szegda, Campbell, Martin, & Insel, 2003), and PFC development (Braun, Lange, Metzger, & Poeggel, 2000). Moreover, susceptibility to stress can be transmitted across generations (Francis & Meaney, 1999), and stressful rearing conditions have even been shown to predict behavior more reliably than genes (Francis et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, findings from several studies have shown that environmental complexity can augment brain development (e.g., van Praag, Emperman, & Gage, 2000;Rosenweig & Bennett, 1996). In contrast, environmental deprivation and stress have been shown to adversely affect behavior (Clarke & Schneider, 1993;Higley et al, 1993), performance on cognitive tests (Francis, Szegda, Campbell, Martin, & Insel, 2003), and PFC development (Braun, Lange, Metzger, & Poeggel, 2000). Moreover, susceptibility to stress can be transmitted across generations (Francis & Meaney, 1999), and stressful rearing conditions have even been shown to predict behavior more reliably than genes (Francis et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We then reduced the full model by sequentially removing the least important covariates and then re-fitting the model. Change in oxygen concentration (a) for each chamber was calculated as the slope (DO 2saturation /Dt), and oxygen consumption rate (MO 2 is the volume of each chamber minus number of eggs by volume of eggs in chamber (ml), b the oxygen solubility (adjusted for temperature and barometric pressure) and M b 21 the clutch mass (kg) before placing in chamber [30].…”
Section: Methodsmentioning
confidence: 99%
“…For example, exposure to predation risk caused female fall field crickets (Gryllus pennsylvanicus) to produce offspring that exhibited more antipredator behaviours [1]. Similarly, prenatally stressed female monkeys produced offspring that clinged together during challenging conditions [2], and the offspring of prenatally stressed rats avoided open locations [3]. A recent study suggested that intergenerational transmission of antipredator behaviour might occur via a hormonal mechanism: snowshoe hare females that were exposed to predation risk by lynx exhibited increased concentrations of glucocorticoids, and produced offspring with a more reactive stress response system [4].…”
Section: Introductionmentioning
confidence: 99%
“…22 In rats, prenatal noise exposure also increased serum corticosterone levels and produced abnormal behavior. 23 In humans, maternal placental lactogen was significantly lower after 36 weeks of gestation in women subjected to airport noise than women living in quiet areas.…”
Section: Potential Fetal Effectsmentioning
confidence: 99%